Gel-like properties of MCM-41 material and its transformation to MCM-50 in a caustic alkaline surround - Saputra, Hens; Othman, Raihan; Sutjipto, Agus Geter Edy; Muhida, Riza; Ani, Mohd Hanafi (Elsevier, 2012)
MCM-41 material, prepared by sol–gel method, reveals gel-like properties in a caustic alkaline environment, i.e., 6 M potassium hydroxide (KOH) electrolyte. The gellation of MCM-41 starts at a KOH weight ratio of 40 wt.%. The structural change of the material is verified with X-Ray diffractograms and supported by observation using Scanning Electron Microscope (SEM). As the KOH weight ratio increases, the MCM-41 hexagonal arrays structure gradually transforms into MCM-50 lamellar structure before disappearing completely at 80 wt.% KOH. The MCM gel phase is further characterized by rotational viscometry and texture analysis. The gel phase shows shear thinning or pseudoplastic behavior and possesses homogeneous matrix structure.